Efektivitas Pembelajaran Kooperatif Tipe Think Pair Share untuk Meningkatkan Hasil Belajar IPA di MTs N Gondowulung - Asih Budiati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2018)
This research aims to know the effectiveness of cooperative learning types Think Pair Share (TPS) to improve the learning results of IPA specifically material chemicals in Life in class VIII-B MTsN Gondowulung. This research is a research action class that is intended to address the existing problems in the classroom by utilizing real action and then do a reflection against the results of the action. This research takes place in two cycles. Each cycle consists of two meetings, each cycle is implemented with four stages: planning, implementation, observation, action and reflection. The subject of this research is grade VIII-B MTsN Bantul Gondowulung that add up to 34 students. Data collection methods used are observation, documentation, and test the results of the study. Data obtained in the field dinalisis using qualitative analysis techniques by means of categorisation/categorization includes the reduction of data, data retrieval and presentation of conclusions. The results showed that the implementation of cooperative learning types Think Pair Share (TPS) in class VIII-B MTsN Bantul Gondowulung can improve the learning results of the IPA especially chemical material in life. It can be seen from the results of the students in class study on Deuteronomy I its daily average is 56.76 on Deut. II daily mean value was 48.97 and Deuteronomy III daily average was 58.38. While the average rating on a cycle I was 65.44 as well as an average rating on cycle II is 71.34. The increase in value from the beginning of 56.76 Deuteronomy daily be 71.32 on the test cycle II shows the increase of 14.56. Activities or the activities of students during the study also experienced an increase, this is indicated by the percentage of students who are actively increasing from the first meeting through to the four i.e. 60.29% at the first meeting, 66.91 at the meeting keduan, 72.30% at the meeting, the third and fourth meeting at 74.26%. Thus it can be said that cooperative learning types think pair share (TPR) is very effective to improve the learning results of the IPA.